The impact of zero markup drug policy on patients' healthcare utilization and expense: An interrupted time series study - Zhu, Zheng; Wang, Junfeng; Sun, Yan; Zhang, Jiawei; Han, Peien; Yang, Li (Frontiers in Medicine, 2022)
Objective To curb the unreasonable growth of pharmaceutical expenditures, Beijing implemented the zero markup drug policy (ZMDP) in public hospitals in 2017, which focused on separating drug sales from hospital revenue. The purpose of this study is to evaluate the impacts of ZMDP on healthcare expenditures and utilization for inpatients. Methods The Beijing claims data of inpatients diagnosed with ischemic heart disease (IHD), chronic renal failure (CRF), and lung cancer (LC) was extracted from the China Health Insurance Research Association (CHIRA) database. The study employed an interrupted time series to evaluate the impacts of ZMDP on healthcare expenditures and utilization. Results The changes in total hospitalization expenses, health insurance expenses, and out-of-pocket expenses were not statistically significant neither in level change nor in trend change for inpatients diagnosed with IHD, CRF, or LC after implementing ZMDP (all P > 0.05). The Western medicine expenses for the treatment of inpatients diagnosed with IHD significantly decreased by 1,923.38 CNY after the reform (P < 0.05). The Chinese medicine expenses of inpatients diagnosed with CRF instantaneously increased by 1,344.89 CNY (P < 0.05). The service expenses of inpatients diagnosed with IHD and LC instantaneously increased by 756.52 CNY (p > 0.05) and 2,629.19 CNY (p < 0.05), respectively. However, there were no significant changes (P > 0.05) in out-of-pocket expenses, medical consumables, imaging, and laboratory test expenses of inpatients diagnosed with IHD, CRF, or LC. The initiation of the intervention immediately increased the number of inpatient admissions with LC by 2.293 per month (p < 0.05). Conclusions The ZMDP was effective in reducing drug costs, and the effects on healthcare utilization varied across diseases type. However, the increase in medical service and Chinese medicine expenses diminished the effect of containing healthcare expenses and relieving the financial burdens of patients. Policymakers are advised to take multiple and long-lasting measures, such as provider payment methods reform, volume-based drug procurement, and drug price negotiation to improve the affordability of patients thoroughly.